2021
DOI: 10.3390/d13080398
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Signaling in Vertebrate Hindbrain Segmentation: Evolution and Diversification

Abstract: In metazoans, Hox genes are key drivers of morphogenesis. In chordates, they play important roles in patterning the antero-posterior (A-P) axis. A crucial aspect of their role in axial patterning is their collinear expression, a process thought to be linked to their response to major signaling pathways such as retinoic acid (RA) signaling. The amplification of Hox genes following major events of genome evolution can contribute to morphological diversity. In vertebrates, RA acts as a key regulator of the gene r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 316 publications
(473 reference statements)
0
9
0
Order By: Relevance
“…These nested domains of expression generate a combinatorial Hox code, which provides a molecular framework that serves as a key regulatory step in specifying regional identities and properties of tissues that serves as a key regulatory step in specifying regional identities and properties of tissues along the A-P axis. A wide variety of studies in different species and cell culture models have revealed that the nested domains of Hox expression along the A-P axis arise in part through the ability of Hox clusters to integrate and respond to opposing signaling gradients, such as those of Retinoic acid (RA), Fibroblast growth factors (Fgfs) and Wingless related integration sites (WNTs) [5,[17][18][19][20][21][22][23][24][25][26][27][28][29]. Hence, it is important to understand the regulatory mechanisms through which signaling pathways are able to coordinately control the precise patterns of the transcription of the clustered Hox genes required for their roles in specifying diverse morphologic features along the A-P axis.…”
Section: Introductionmentioning
confidence: 99%
“…These nested domains of expression generate a combinatorial Hox code, which provides a molecular framework that serves as a key regulatory step in specifying regional identities and properties of tissues that serves as a key regulatory step in specifying regional identities and properties of tissues along the A-P axis. A wide variety of studies in different species and cell culture models have revealed that the nested domains of Hox expression along the A-P axis arise in part through the ability of Hox clusters to integrate and respond to opposing signaling gradients, such as those of Retinoic acid (RA), Fibroblast growth factors (Fgfs) and Wingless related integration sites (WNTs) [5,[17][18][19][20][21][22][23][24][25][26][27][28][29]. Hence, it is important to understand the regulatory mechanisms through which signaling pathways are able to coordinately control the precise patterns of the transcription of the clustered Hox genes required for their roles in specifying diverse morphologic features along the A-P axis.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate potential roles for RA signaling in hindbrain development of the sea lamprey ( Petromyzon marinus, Pm ), we first identified members of gene families predicted to encode components of the enzymatic machinery involved in synthesis (Aldh1a) and degradation (Cyp26) of retinoids associated with neural tube development in jawed vertebrates 26 . We identified three predicted Cyp26-like genes in the sea lamprey germline genome assembly (KPetmar1) 44 , 45 , Cyp26A1 , C yp26B1/C1a , and Cyp26B1/C1b , and two Aldh1a-like genes, Aldh1a1/a2a and Aldh1a1/a2b .…”
Section: Resultsmentioning
confidence: 99%
“…These markers have been used in previous studies 34 , 39 , 42 , 63 and provide a readout of the molecular regionalization that demarcates neuroepithelial segments. To assess the effect of these treatments on hindbrain segmentation, we performed cISH on the drug-treated embryos using probes for key genes involved in hindbrain patterning: a) otx and wnt1 mark subdivision of the forebrain and midbrain 26 ; b) krox20 and kreisler are segmental subdivision genes that mark the r3/r5 and r5/r6 territories, respectively 34 , 42 ; and c) hoxβ1 , hoxα2 , hoxα3, hoxζ4 are segmental identity genes each marking different groups of rhombomeres (Fig. 5a ) 42 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations